ACADEMIC PRESSURE AND CAFFEINE: USAGE TRENDS AMONG UNDERGRADUATES DURING THE PANDEMIC - Williams, Emily Grace; Johnson, David Alexander (International Research Journal Diagnostics, 2024)
Caffeinated beverages have long been a staple for college students, raising concerns about caffeine overuse. A recent survey conducted across five U.S. universities revealed a staggering 92% of students reporting caffeine consumption in the past year. This trend is on the rise, largely attributed to a lack of education regarding overconsumption. Notably, the primary source of caffeine among college students, regardless of gender, was found to be coffee. The study, "Intake of caffeine from all sources and reasons for use by college students," conducted by Mahoney and colleagues, not only identified coffee as the preferred choice but also provided insights into demographic factors influencing caffeine consumption. Age, gender, family income, and ethnicity were considered to assess how caffeine consumption varies among different student groups. While the Food and Drug Administration (FDA) recognizes caffeine as a potential component of a healthy diet, caution is warranted. Excessive caffeine intake can pose health risks, particularly contingent on factors such as body weight, medication use, and elevated stress levels. This abstract sheds light on the prevalence of caffeine consumption among college students, its growing trend, and the importance of informed caffeine use, considering individual health circumstances.